2021
DOI: 10.3389/fimmu.2021.670279
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plant Leaf Extract From Sage and Lemon Verbena Promotes Intestinal Immunity and Barrier Function in Gilthead Seabream (Sparus aurata)

Abstract: The inclusion of a medicinal plant leaf extract (MPLE) from sage (Salvia officinalis) and lemon verbena (Lippia citriodora), rich in verbascoside and triterpenic compounds like ursolic acid, was evaluated in gilthead seabream (Sparus aurata) fed a low fishmeal-based diet (48% crude protein, 17% crude fat, 21.7 MJ kg-1, 7% fishmeal, 15% fish oil) for 92 days. In particular, the study focused on the effect of these phytogenic compounds on the gut condition by analyzing the transcriptomic profiling (microarray an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 114 publications
(116 reference statements)
1
13
0
Order By: Relevance
“…In the present study, we evaluated the potential benefits of the dietary administration of SDPP in the gut of a marine teleost species by a detailed transcripteractome built from the enriched biological processes obtained to elucidate how this functional ingredient acted upon the maintenance of the gut mucosal tissue. Transcripteractome-based functional network analysis on teleost fish has gained attention in the last years (Firmino et al, 2020(Firmino et al, , 2021aReyes-López et al, 2021;Salomón et al, 2021). Previously, a similar strategy was followed by Reyes-López et al (2021) to analyze the effects of SDPP at skin level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we evaluated the potential benefits of the dietary administration of SDPP in the gut of a marine teleost species by a detailed transcripteractome built from the enriched biological processes obtained to elucidate how this functional ingredient acted upon the maintenance of the gut mucosal tissue. Transcripteractome-based functional network analysis on teleost fish has gained attention in the last years (Firmino et al, 2020(Firmino et al, , 2021aReyes-López et al, 2021;Salomón et al, 2021). Previously, a similar strategy was followed by Reyes-López et al (2021) to analyze the effects of SDPP at skin level.…”
Section: Discussionmentioning
confidence: 99%
“…A small piece of the anterior intestine (0.5 cm) was dissected and immediately transferred into RNAlater (Ambion R ) incubated at 4 • C overnight and frozen at −80 • C until further RNA extraction. The anterior intestine was chosen because of its immunological relevance in comparison with other intestinal sections (Oehlers et al, 2011;Salomón et al, 2021). Fish growth and feed utilization from Control and SDPP groups were evaluated using the following indices: Fulton's condition factor (K) = (BW/SL 3 ) × 100; specific growth rate in BW (SGR,%) = [(ln BWf −ln BWi) × 100]/time (d) and feed conversion ratio (FCR, g/g) = FI/(Bf −Bi), where FI was the total feed intake during the experimental period (g) and, Bi and Bf were the initial and final biomass (g), respectively.…”
Section: Fish and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…These functional properties make them very attractive for the industry as potential prophylactic dietary treatments. In particular, the current investigation endeavors to explore the dietary effects of phytogenics derived from a mixture of medicinal plants, the sage (Salvia officinalis, Lamiaceae) and the lemon verbena (Lippia citriodora, Verbenaceae), both recognized for their health and growth-promoting properties for aquatic species (Elumalai et al, 2020;Salomón et al, 2020Salomón et al, , 2021a. In particular, in a previous study from our group, we showed that a medicinal plant leaf extract (MPLE) from sage and lemon verbena promoted an improvement in the classical key performance indicators (KPIs) linked to somatic growth and feed efficiency.…”
Section: Introductionmentioning
confidence: 99%